Self-care nursing assessment: cross-cultural adaptation and validation of the Spanish version of the Self-care of chronic illness inventory - Noelia Durán-Gómez; Casimiro Fermín López-Jurado; Miguel Ángel Martín-Parrilla; Jesús Montanero-Fernández; Demetrio Pérez-Civantos; Macarena C. Cáceres (BMC Nursing, 2023)
Abstract Background Self‐care is the primary means of caring for a chronic condition. Therefore, it is necessary to assess it by using a good validity and reliability instrument. The Self-Care of Chronic Illness Inventory (SC-CII) is a generic instrument developed to measure self-care processes behaviors using three separate scales in patients with chronic illness. The original cross-cultural assessment concluded the need for future studies sampling patients from different sites to increase the generalizability of the psychometric evaluation results. It was unclear whether this tool had sound psychometrics properties in the context of Spanish culture. The purpose of this study was to cross-culturally adapt the SC-CII, test its psychometric properties and validate its use among Spanish people with chronic diseases. Methods A cross-cultural translation of the SC-CII was performed from English to Spanish. The psychometric evaluation was conducted in a sample of 350 patients with chronic conditions through a multicenter cross-sectional study based on the STROBE guideline. Data were collected from face-to-face interviews during 2022. Internal validity was assessed with Confirmatory Factor Analysis, internal consistency reliability with Cronbach alpha for unidimensional scales and McDonald's Omega reliability coefficient for multidimensional scales. Results Most (63.4%) participants were older adults aged 65 years or older with a mean age of 65.45 ± 14.97. The average number of chronic conditions reported was 2.81%; the most common conditions were hypertension (52.3%), musculoskeletal disorders (46.3%) and diabetes (38.9%). Patients reported adequate self-care behaviors in all three scales of the SC-CII. The Self-Care Maintenance and Management scales were multidimensional, and the Self-Care Monitoring scale was unidimensional. In Confirmatory Factor Analysis, the Self-Care Maintenance and Monitoring scales had satisfactory fit indices. The Self-care Management scale had acceptable fit indices. The Omega reliability coefficient for multidimensional scales was 0.75 (Self-Care Maintenance) and 0.72 (Self-Care Management). The Cronbach alpha coefficient of the Self-Care Monitoring scale was 0.85. Item-total correlations were all significant except one. Test–retest reliability showed an intraclass correlation coefficient of 0.92. Conclusions The SC-CII has appropriate psychometrics characteristics and is a culturally suitable and reliable instrument for assessing to the self-care behaviors of patients with chronic disease in Spain. The scale provides a simple and rapid solution to assess the self-care process.